Development of M1 smart card as an anti-corruption education media in SD Muhammadiyah Surakarta - Suyitno; Suyadi; Dikdik Baehaqi Arif; Abdulaziz Kalupae (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
In response to the urgent corruption issue in Indonesia, which is reflected in the Corruption Perception Index (CPI) 2024 score of 34, the present study was conducted. One preventive effort is anti-corruption education at SD Muhammadiyah Ketelan Surakarta, a school designated by the Indonesian Corruption Eradication Commission (KPK) as a Pilot School for Anti-Corruption Education. The M1 Smart Card was developed as a learning medium based on anticorruption values to support this. This study aims to (1) examine the development of the M1 Smart Card, (2) analyse its implementation in the learning process, and (3) evaluate its impact on students’ behaviours. Using a qualitative approach with observations, interviews, and documentation, data were analysed through Miles and Huberman’s model. The findings reveal that (1) the M1 Smart Card was collaboratively designed to integrate character values, (2) it has been consistently implemented through school culture and classroom practices, and (3) its application fosters honesty by functioning as a zero-cheating tool, leading to a noticeable increase in students’ awareness, responsibility, and integrity in daily learning activities. This research contributes to the field of elementary education by providing evidence of how an innovative, value-based learning medium can strengthen anti-corruption character education and serve as a practical model for other schools.